Prospecção e expressão de uma enzima proteolítica a partir de uma biblioteca metagenômica do consórcio microbiano degradador de óleo diesel - Silveira, Bianca de Melo [UNESP] (2015)
From a metagenomic library of a microbial consortium that degrades diesel oil, a clone (PL3C3) expressing a novel protease gene was selected from twenty six positive for azocasein degradation. Through sequencing, an analysis was made contig and identified an ORF encoding a protein, called ORF19 composed of 966 bp, 321 amino acids, exhibiting 69% identity with an alpha / hydrolase beta Parvibaculum lavamentivorans DS-1 (accession number ABS62095. 1). The sequence of ORF19 after analysis of a protease database - MEROPS - showed 74.3% identity with a serine protease family S9U (access number MER095859). Through phylogenetic analysis, it was possible to suggest that ORF19 is a new member of this family displaying the catalytic triad and characteristic conserved motifs. The molecular mass of the protein was estimated at 35 KDa, based on its amino acid composition and estimates Protparam by the program, and considering the pattern of electrophoretic migration of the protein under denaturing conditions. The ORF19 gene was cloned into the pET28a expression vector, but not the recombinant protein was overexpressed in E. coli BL21 (DE3). However, the exchange of host, vector, and studies for overexpression is required to obtain the protein, for their further characterization. This study contributes to the discovery of a new serine protease using molecular approaches, as metagenomic